2017
DOI: 10.1007/s00787-017-1058-z
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind placebo-controlled randomised trial of omega-3 supplementation in children with moderate ADHD symptoms

Abstract: This study did not show any beneficial effect of omega-3 supplement in children with mild ADHD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 28 publications
0
40
0
1
Order By: Relevance
“…For additional analyses. Systematic reviews and other studies of this question provide inconsistent results, as they include heterogeneous groups of participants, interventions, comparators and outcomes [ 10 , 11 , 16 20 ]. Furthermore, there are implementation differences in dose, delivery, uptake and context both generally [ 35 ], specifically to this field [ 36 ], and with regard to this trial as discussed (see above).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For additional analyses. Systematic reviews and other studies of this question provide inconsistent results, as they include heterogeneous groups of participants, interventions, comparators and outcomes [ 10 , 11 , 16 20 ]. Furthermore, there are implementation differences in dose, delivery, uptake and context both generally [ 35 ], specifically to this field [ 36 ], and with regard to this trial as discussed (see above).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this review also pointed to the lack of comparable studies reporting reading as an outcome. Since then a few smaller trials found no effects for ADHD [ 11 ] however positive effects on spelling [ 12 ] and comprehensive assessments of reading ability in mainstream Scandinavian children [ 13 , 14 ] have been found, while other trials obtained insufficient evidence in these domains [ 15 ]. However, these studies test combinations of PUFAs with e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A recent randomized placebo-controlled trial evaluating the efficacy of omega-3 PUFAs in children and adolescents with ADHD over three months found that the total reduction in an ADHD rating score was significantly greater in the placebo group than in the PUFA group (Cornu et al, 2018). Moreover, the pooling of these data with previously published results demonstrated no overall effect of omega-3 PUFAs on ADHD symptoms (Cornu et al, 2018).…”
Section: Findings On Food Bioactives In Adhdmentioning
confidence: 97%
“…A systematic review of metaanalyses of double-blind placebo-controlled trials showed that the effect sizes for PUFA supplementation were small in regard to the ratings of ADHD symptoms by parents and teachers (Pelsser et al, 2017). A recent randomized placebo-controlled trial evaluating the efficacy of omega-3 PUFAs in children and adolescents with ADHD over three months found that the total reduction in an ADHD rating score was significantly greater in the placebo group than in the PUFA group (Cornu et al, 2018). Moreover, the pooling of these data with previously published results demonstrated no overall effect of omega-3 PUFAs on ADHD symptoms (Cornu et al, 2018).…”
Section: Findings On Food Bioactives In Adhdmentioning
confidence: 99%
“…ADHD symptoms (20). Accordingly, there is currently little support for the efficacy of omega-3 PUFA supplementation on the core symptoms of ADHD.…”
mentioning
confidence: 99%